1999
DOI: 10.1001/archotol.125.7.758
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Passive Cigarette Smoking to Otitis Media

Abstract: Passive smoking increases the risk of OME and ROM in children between 3 and 7 years old. The avoidance of daily exposure to domestic tobacco smoke could have a public health impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(9 citation statements)
references
References 26 publications
(26 reference statements)
1
7
0
Order By: Relevance
“…This increased likelihood is consistent with findings in other studies [17, 18, 49] during the first year of life. Still others have failed to establish a positive association between maternal smoking and otitis media [5052].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This increased likelihood is consistent with findings in other studies [17, 18, 49] during the first year of life. Still others have failed to establish a positive association between maternal smoking and otitis media [5052].…”
Section: Discussionsupporting
confidence: 93%
“…A number of studies have attempted to describe the relationship between postnatal exposure to secondhand smoke and otitis media; however, there has been little agreement between them. Some studies indicate a clear association between secondhand smoke exposure and otitis media [17]. In particular, heavy maternal smoking is associated with an increased risk for ROM in the first year of life for infants weighing less than 3500 grams at birth [18].…”
Section: Introductionmentioning
confidence: 99%
“…Table 3 shows that there was inconsistency between studies on the impact of ETS exposure on prognosis after ENT surgical procedures. Three studies 32 38 39 showed no significant effects on outcomes, although two studies suggested some evidence that ETS exposure decreased the effectiveness or duration of tympanostomy (ventilation) tubes. 28 35 Other studies showed ETS exposure caused a potential deterioration of either subjective 29 34 36 or objective 30 31 33 40 outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Oxygen desaturations 18 20 22 27 and muscle relaxant dosages 21 were used as biological measures. Long-term surgical outcome markers included ciliary regeneration, 30 as well as clinical measures such as change in symptoms and signs, 34 36 39 complications 32 35 40 or repeat procedures. 34 38 …”
Section: Resultsmentioning
confidence: 99%
“…OME is a condition in which fluid is retained in the middle ear cavity but without otalgia, fever, or other symptoms (2). This condition has been shown to be caused by complex reactions involving the dysfunction of the Eustachian tubes, infection in the mucosa, immune deficiency, and allergy, among others (3). The incidence of OME varies widely, being reported as 50% in British children (4), 8.7% in Japanese children (5), 8% in Nigerian children (6) with differences according to surveyed regions.…”
Section: Introductionmentioning
confidence: 99%